Characterization of the volatiles and quality of Ningxiang pork belly and their relationship to changes of microbial community during chilled storage - Ziyi Hu; Liusha Kuang; Lin Li; Enqi He; Lei Zhou; Aihua Lou; Yan Liu; Jie Luo; Wei Quan; Qingwu Shen (CyTA - Journal of Food)
The correlations between meat quality, dominant microbiota, and key volatile compounds during chill storage were investigated by HS-SPME-GC-MS, Illumina sequencing and correlation analysis. The results indicated that lipid and protein oxidation of pork belly increased significantly on day 4, biogenic amine index reaching 344.07 mg/kg on day 6, the total viable count reached 7.98 log10 (CFU/g) at day 8, with Macrococcus caseolyticus (54.60%), unclassified g Acinetobacter (23.70%) and Acinetobacter bereziniae (7.75%) identified as dominant bacteria. HS-SPME-GC-MS identified 66 compounds with tetramethyl-pyrazine, acetoin, 1-hexadecanol, and hexadecanoic acid were found to be related to meat quality and influenced by microbial activity, serving as indicators of pork belly freshness. However, due to the complexity of microbial communities in aquatic products, further research is needed to explore the relationship between changes in microbial communities and the volatile organic compounds (VOCs). These findings provide valuable insight into key factors contributing to spoilage in Ningxiang pork.